USE OF EXTERNAL SKELETAL FIXATORS IN THE DOUBLE PELVIC OSTEOTOMY TECHNIQUE IN DOGS - Panta V., José (2013)
The aim of this study was to evaluate the use of external skeletal fixators as a means of stabilization, using the technique of double pelvic osteotomy in patients with hip dysplasia. Five crossbred dogs (3 males and 2 females), 3-4 months old, weighing 9.4 to 12.5 kg, and clinically healthy were used. The Norberg angle was radiological assessed before and after 6 weeks of the surgery when the external fixators were removed. Weekly X-rays for five weeks after the surgery were taken to monitor the development of the bone callus. The 80% (4/5) of dogs showed radiographic evidence of bone callus formation on week 2 and all dogs showed a well-developed bone callus associated with adequate contribution of mechanical stability on week 5. The Norberg angle increased 9.4 degrees on average (Range: 4 to 14 degress). The results showed that external skeletal fixation provides good stability when using the double pelvic osteotomy.